PTH-028 Gastro-intestinal symptoms in candidates for bariatric surgery. (23rd September 2015) - Alexandropoulou, K; Lucena, H F Medina; Reddy, M; Wan, A; Poullis, A; Kang, J
Abstract : Introduction: Obesity and related medical conditions are an increasing problem in the West. British National Institute of Clinical Excellence guidelines recommend the use of bariatric surgery for morbidly obese patients with a body mass index (BMI) of 40 kg/m 2 or more, and for patients with a BMI 35–40 kg/m 2 who have complicating comorbidity that may be improved by weight loss. The prevalence of gastro- oesophageal reflux disease, Barrett's oesophagus and oesophageal adenocarcinoma is increased in obese individuals. Obesity is also related to psychosocial morbidity and psychological problems which in turn predispose to functional gastrointestinal complaints. We investigated the prevalence of gastro-intestinal symptoms in candidates for bariatric surgery at the time of their pre-operative assessment and 3 months post bariatric surgery. Methods: Bariatric surgery candidates were asked to complete a locally validated Rome II questionnaire and the Hospital Anxiety and Depression Scale (HAD) at the time of their pre-assessment. The same questionnaires were sent out by post to these patients 3 months after surgery. Their weight and any changes in medication were also recorded at that stage. Pearson's χ 2 test and Fisher's exact tests (SPSS V.16) were used for statistical analysis. Results: Thirty-nine of 58 patients approached pre-operatively completed the study. There were 33 women and 6 men, mean age of 45 years (range 25–60). Thirty five patients (90%) underwent laparoscopic roux-en-Y gastric bypass, RYGB, (30F/5M), three (8%) had a sleeve gastrectomy (2F:1M) and one had intragastric balloon insertion (1F). Mean time of follow-up was 3.4 months. Thirty-eight patients who lost weight (mean 24.5 kg) were included in this analysis. Their mean BMI was 47 kg/m 2 preoperatively and 38.3 kg/m 2 on follow-up. There was a significant reduction in the frequency of heartburn, reported by 11 patients pre-op and only two post-operatively, p<0.05 (RR 5.5, 95% CI 1.3 to 23.2). Post-operatively, significantly more patients reported dysphagia, dyspepsia and vomiting (p<0.05). There was no difference pre and post operatively in frequency of IBS, constipation, diarrhoea, biliary or anorectal disorders. HAD scores for anxiety were similarly unchanged. Although the frequency of depression was reduced by half (from 10.5% to 5.3%) the difference did not reach statistical significance. Conclusion: The frequency of heartburn was reduced post bariatric surgery. Dysphagia, dyspepsia and vomiting increased in the first 3 months post-operatively.